AB0978 Decreased pain and improved dynamic knee instability mediate the beneficial effect of wearing a soft knee brace on activity limitations in persons with knee osteoarthritis. (12th June 2018) - Cudejko, T.; van der Esch, M.; van den Noort, J.; Rijnhart, J.; van der Leeden, M.; Roorda, L.D.; Lems, W.; Harlaar, J.; Waddington, G.; Dekker, J.
Abstract : Background: We have previously shown that wearing a soft knee brace reduced activity limitations in persons with knee osteoarthritis (OA). 1 Several underlying mechanisms have been proposed via which a soft knee brace reduces activity limitations in persons with knee OA. 2 However, to our knowledge, no study has identified mechanisms explaining this effect. Objectives: The aim of the study was to identify mechanisms explaining the beneficial effect of wearing a soft knee brace on activity limitations in persons with knee OA. Methods: This was an exploratory analysis of data from 44 participants with knee OA from Amsterdam Osteoarthritis cohort, who enrolled in a single-session within-subject cross-over design study, comparing a soft brace with no soft brace, and comparing a non-tight soft brace with a tight soft brace (GENUTEX A2, Human I). A mediation analysis was performed and the mediation effect was calculated based on the product of coefficients approach. Confidence intervals were calculated with a bootstrap procedure. The outcome measures were activity limitations assessed with the 10-metre walk test and the Get up and Go test. The studied mediators were the changes in: knee joint proprioception, pain, pressure pain threshold (PPT) and objective dynamic knee instability. Knee joint proprioception was assessed by the active movement extent discrimination assessment; pain with the Numeric Rating Scale (NRS); PPT with a hand-held pressure algometer, and dynamic knee instability with the Perturbation Response i.e. a measure reflecting deviation in the mean knee varus-valgus angle after a controlled mechanical perturbation on the treadmill, in respect to level walking. Results: Both a decrease in pain during walking and a decrease in dynamic knee instability mediated the association between wearing a soft knee brace and reduction in time to complete both 10 m walk test and the GUG test (p<0.05). Changes in proprioception and PPT did not mediate these associations (p>0.05). Magnitudes of the mediation effects were similar for a non-tight and a tight soft knee brace. Conclusions: The decrease in activity limitations in persons with knee OA who wear a soft knee brace might be explained by a decrease in self-reported pain and a reduction in dynamic knee instability. References: [1] Cudejko T, van der Esch M, van der Leeden M, van den Noort JC, Roorda LD, Lems W, Twisk J, Steultjens M, Woodburn J, Harlaar J, Dekker J: The immediate effect of a soft knee brace on pain, activity limitations, self-reported knee instability, and self-reported knee confidence in patients with knee osteoarthritis. Arthritis Res Ther2017;19:260. [2] Cudejko T, van der Esch M, van der Leeden M, Roorda LD, Pallari J, Bennell KL, Lund H, Dekker J: Effect of Soft Braces on Pain and Physical Function in Patients With Knee Osteoarthritis: Systematic Review With Meta-Analyses. Arch Phys Med Rehabil2018;99:153–163. Disclosure of Interest: None declared